Tumescent Local Anesthesia in Parotid Abscess - Novel Application of Old Technique - Raghuraman, M. S.; Gopi, S.; Radhakrishnan, A.; Madhu, G.; Ishwaryarajan, M. S.; Selvam, P. (Kathmandu University Medical Journal, 2021)
Tumescent local anesthesia (TLA) is a regional anesthetic technique in which the diluted local anesthetic drug (commonly lidocaine) and epinephrine solution in large volume is injected subcutaneously around the site of incision. The main advantages of TLA are excellent bloodless field and longer duration of analgesia because of addition of epinephrine. Although TLA was used in various surgical procedures, there is no literature to date that has reported its use in the parotid region. Hence, we present an interesting case where this old technique found a novel application in avoiding general anesthesia and its sequelae. We also believe that it provides valuable information to doctors of various categories such as surgeons, Anesthesiologists and general practitioners/family physicians.